Musyawarah dalam Perspektif Al-Quran - Ahmad Agis Mubarok (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2019)
Deliberation is part of the teachings of Islam that already exist and are practiced by the Prophet Muhammad and his companions. The order to carry out this meeting is found in the Asy-Syuraa verse 38 and Ali Imran verse 159. Allah gives more attention to this deliberation, namely by giving the name Ash-Shura (deliberation) in one of the letters in the Qur'an. This proves the importance of deliberation in overcoming every issue of life. But not all life problems become objects or fields of deliberation. Only matters relating to social affairs can be used as objects of deliberation, while the affairs of Religion, which already have a text in the Qur'an, cannot be used as objects of deliberation. In this article, the author will explain the interpretations of Al-Maragi, Al-Baghawi, and Ibn Kathir on the verse about deliberation, then show the similarities and differences between the three.